Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru PAI Di SMA Negri 1 Medan - Siti Ramadhani; Tumiran Tumiran (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
The purpose of this study is to find out (1) How the Principal's leadership in improving the performance of PAI teachers at SMA Negeri 1 Medan, (2) to determine the supporting and inhibiting factors of the Principal's leadership in improving the performance of PAI teachers at SMA Negeri 1 Medan. This research is a field research. The method used in this study is qualitative with a qualitative descriptive approach and includes a type of qualitative research that produces descriptive data in the form of written or spoken words. Research data sources are primary and secondary data and data collection techniques by conducting observations, interviews, and documentation. The main findings indicate that visionary, empowering, and collaborative leadership plays a significant role in motivating Islamic Education (PAI) teachers to achieve higher standards. The implication of this study is the need for leadership competency development for school principals and the enhancement of collaboration between school leadership and teaching staff to achieve better educational goals.